Pentingnya Membangun Budaya Literasi (Budaya Membaca) pada Anak SD di Era Digital - Alpiana Puji Astuti; Siti Istianingsih; Arif Widodo; Alpiana Puji Astuti; Siti Istianingsih (Universitas Negeri Malang, 2022)
Abstract: The sophistication of the development of digital technology has an influence on the literacy culture which has begun to erode, especially in the reading culture of the community, especially in elementary school-aged children. Excessive use of gadgets in addition to having an impact on physical health, this can also affect the level of motivation or interest in reading children. Therefore, it is necessary to increase the literacy culture in children accompanied by support from various parties such as parents, teachers and the government. This research uses the literature study method by reviewing and collecting various sources of information from several scientific articles. The purpose of writing this article is to find out the literacy culture of the digital era, find out the importance of growing a reading literacy culture in elementary school children, and efforts to grow a literacy culture. The results presented in this study are cultural literacy has an important role for the growth of characteristics and development of children both in knowledge and in life. Abstrak: Canggihnya perkembangan teknologi digital memiliki pengaruh terhadap budaya literasi yang sudah mulai terkikis khususnya pada budaya membaca masyarakat terutama pada anak usia sekolah dasar. Penggunaan gadget yang berlebihan selain berdampak pada kesehatan fisik, hal ini juga dapat mempengaruhi tingkat motivasi atau minat baca anak. Oleh karena itu,perlu adanya peningkatan budaya literasi pada anak disertai dukungan dari berbagai pihak seperti,orang tua,guru dan pemerintah. Penelitian ini menggunakan metode studi pustaka dengan mengkaji serta mengumpulkan berbagai sumber informasi dari beberapa artikel ilmiah. Tujuan dari penulisan artikel ini adalah untuk mengetahui budaya literasi era digital, mengetahui pentingnya penumbuhan budaya literasi membaca pada anak sekolah dasar, dan upaya penumbuhan budaya literasi. Hasil yang dikemukakan dalam penelitian ini adalah budaya literasi memiliki peranan penting bagi penumbuhan karakteristik serta perkembangan anak baik dalam pengetahuan maupun kehidupannya.